1991
DOI: 10.1073/pnas.88.13.5789
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assay of the chlorophyll biosynthetic enzyme Mg-chelatase: resolution of the activity into soluble and membrane-bound fractions.

Abstract: The fist committed step in chlorophyll synthesis is the Mg-chelatase-catalyzed insertion of magnesium into protoporphyrin IX. Since iron insertion into protoporphyrin leads to heme formation, Mg-chelastase lies at the branch point of heme and chlorophyll synthesis in chloroplasts. Little is known about the enzymology or regulation of Mg-chelatase, as it has been assayed only in intact cucumber chloroplasts. In this report we describe an in vitro assay for Mg-chelatase.Mg-chelatase activity in intact pea chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 17 publications
1
58
3
Order By: Relevance
“…In contrast, Mg-chelatase has resisted attempts at characterization for many years and has proved to be a much more difficult enzyme to analyse. The major impediment was the lack of an in itro assay, which was only achieved 6 years ago [2]. Since that time our knowledge of Mg-chelatase has expanded dramatically to the extent that the enzyme has been cloned and sequenced from several photosynthetic species [3][4][5][6][7][8][9][10].…”
Section: Scheme 2 Reaction Catalysed By Mg-chelatasementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Mg-chelatase has resisted attempts at characterization for many years and has proved to be a much more difficult enzyme to analyse. The major impediment was the lack of an in itro assay, which was only achieved 6 years ago [2]. Since that time our knowledge of Mg-chelatase has expanded dramatically to the extent that the enzyme has been cloned and sequenced from several photosynthetic species [3][4][5][6][7][8][9][10].…”
Section: Scheme 2 Reaction Catalysed By Mg-chelatasementioning
confidence: 99%
“…The reason for the loss of activity on breakage became apparent when high in itro levels of Mg-chelatase activity were reported for lysed pea (Pisum sati um) chloroplasts [2]. The key to preserving activity was to lyse chloroplasts at a high protein concentration so as not to dilute the chloroplast contents.…”
Section: Demonstration Of Mg-chelatase Activity In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Walker and Weinstein (1991b) demonstrated that Mg chelatase activity required soluble and membrane fractions of lysed pea chloroplasts. They later reported that Mg chelatase activity was rendered entirely soluble if pea chloroplasts were lysed in buffers containing low concentrations of Mg 2+ (Walker and Weinstein, 1995).…”
Section: Localization Of Chl H By Immunoblottingmentioning
confidence: 99%
“…Accordingly, this enzyme has been the subject of much study in plants (Fuesler et al, 1981;Weinstein 1991a, 1991b;Walker and Weinstein, 1994), although purification of the enzyme has proved difficult. At present, it has been possible to establish a continuous assay for the enzyme and to show that two components probably participate in the chelation reaction (Walker and Weinstein, 1991b;Walker and Weinstein, 1995). It is also known that there is an ATP requirement for the activation of these components (Walker and Weinstein, 1994).…”
mentioning
confidence: 99%